International joint ventures and firm value: an empirical study of South African partner firms - Mangwengwende, Tadiwanashe Mukudzeyi (Rhodes University, Faculty of Commerce, Department of Economics, 2013)
This study investigates international equity joint ventures (IJVs) and South African partner firm value creation at formation. In addition, it tests whether four contentious formation characteristics, namely, the geographical location of the IJV partner, the level of economic development in the IJV partner's home country, the level of equity held by the South African firm and the industry of the South African firm, can explain when South African IJVs are value enhancing and when they are value diminishing. IJVs are a popular business mode and an important channel for infrastructure and skills investment in developing countries. However, despite their popularity and potential social benefits, these IJVs are predominantly created by the decisions of private firms to collaborate with foreign firms and governments. Consequently the preservation and development of the IJV investment channel is dependent on the encouragement of private firm IJV participation. It is at uncovering potential tools to encourage IJV participation by South African firms that IJV firm value creation becomes important because it stands as a motivator for South African firms' involvement in IJVs. Existing literature on IJVs and partner firm value has presented conflicting evidence with support for the views that they are value enhancing, value diminishing or of no immediate consequence to their partners' firm value. Consequently, previous research offers limited firm value support for IJVs. For South African firms considering joint ventures and national policy makers determined to promote IJVs there is a need for an investigation of South African partner IJV firm value effects. Moreover, it is also necessary to test potential explanatory variables that may help to explain when the IJVs are value enhancing and when they are not as this will inform IJV contract negotiations and how limited national government resources are used to promote IJVs. In order to assess firm value creation for South African firms this study performed event studies on IJV formation announcements from 1998 to 2011 using daily share returns from the Johannesburg Securities Exchange taking care to incorporate recent developments in the event study methodology. The study found that while the market responds to IJV announcements, its responses do not, on average, reflect that IJVs are firm value enhancing for their South African partners at formation. This stands in contrast to considerable empirical literature and IJV firm value creation theory. In addition, factoring in formation characteristics, argued to potentially help explain cases of value creation and destruction from IJVs, provided limited explanation for positive and negative wealth effectsfor South African firms entering IJVs. This result has important value for IJV participants, national economic policy makers and IJV researchers. For IJV participants and national policy makers, the results caution unfettered entry/support for IJVs and challenge the role of equity distribution in determining the value of the IJV to its partner firms. For IJV researchers, the results present new evidence questioning IJV firm value creation at formation and provide a potential explanation for the conflict in previous IJV research. The study makes four key contributions to the existing knowledge of IJV firm value creation. Firstly, it assesses IJV wealth effects for the hitherto untested South African IJVs. Secondly, in doing so it adds a new data set (South African IJVs) to the current IJV literature. Thirdly, in reviewing the literature on IJV firm value creation the study presents a disaggregated model of IJV firm value creation from which to develop IJV research and potentially solve the persistent conflict in empirical results on IJV partner wealth effects. Finally, it informs future South African IJV agreements by uncovering factors that influence and do not influence partner wealth effects for South African firms.
Keywords: Joint ventures; Joint ventures -- South Africa; Business enterprises -- Valuation; International business enterprises